15 Promoting the need for a dedicated Neuro‑Oncology Occupational Therapy Service at QEHB: A Quality Improvement Project - Megan Jones (Neuro-Oncology, 2026)
Abstract Introduction This project highlights the role of Occupational Therapists (OTs) in supporting the neuro‑oncology patient population at the Queen Elizabeth Hospital Birmingham (QEHB). Although the OT service is well established, there is currently no structured pathway to ensure that patients with brain cancer receive optimal pre‑ and post‑operative management. This patient group is also at risk of inadequate follow‑up after discharge, re-affirming the need for service development and targeted investment. Method A retrospective case‑note review was conducted for all patients with a new or existing brain cancer diagnosis across three Neurosciences wards. Each identified patient received a post‑operative face‑to‑face screening incorporating observational and cognitive assessments. Data is collected and analysed using a standardised Excel spreadsheet. The Quality Improvement Project began in October 2025 and is expected to conclude in March 2026, with an estimated sample size of 100–120 patients. The analysis will help identify common themes and symptoms that require intervention. This will support in identifying which patient groups would benefit most from pre‑ and post‑operative OT assessment, by exploring opportunities for post‑discharge intervention, with the aim in reducing length of stay. Results Preliminary findings indicate a clear need for an enhanced OT service and a dedicated neuro‑oncology pathway at QEHB. Patients with high‑grade gliomas, frontal‑lobe presentations, post‑operative complications, and cognitive‑communication impairments frequently require equipment provision, cognitive and functional assessment, patient education, and MDT referrals. Conclusions Initial data demonstrate a strong clinical justification for a structured OT pathway within the neuro‑oncology service to provide consistent pre‑ and post‑operative assessment, as well as potential post‑discharge follow‑up. These findings will inform future service development and quality improvement efforts. Full data analysis will be completed for presentation at the forthcoming conference.